Shall i help you my dear? Examining variations in social support for career advancement within partnerships - Katrin Golsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Strong gender inequalities persist in the career advancement of men and women. Vertical and horizontal dimensions of segregation, gender role beliefs, and the public provision of welfare services all provide explanations for gender inequalities. Much less is known about the social mechanisms at work within couples, however. Following the notion of linked lives, the present study investigates the provision of social support for career advancement within partnerships. Using data from wave 23 (2006) of the German Socio-Economic Panel Study (SOEP) and considering couples as units of analysis, this study focuses on individual resources and aspirations, intra-couple bargaining as well as on educational and occupational homogamy between spouses. The empirical analysis controls for individual qualifications, characteristics of career development and current job of both partners. Family-specific variables and regional differences are also taken into account. The results of the analysis, although cross-sectional, give some initial insights into patterns of social support within couples.
Keywords: 330; social support; partnership; gender